Giant pants - Fearing, Mark (Candlewick Press, 2017)
After searching high and low for his missing pants, Belbum the giant asks his friends if he can borrow their trousers, but when none of the clothes fit him he realizes there is only one thing left for him to do--walk to the tailor in town with no pants on.